Divergence in hybrid rice parental lines detected by RAPD and ISSR markers - Ghaffar KIANI; Camellia KATALANI (Acta Agriculturae Slovenica, 2018)
Genetic distance between parental lines used in hybrid rice breeding program was estimated based on information from molecular markers data. Sixteen parents (5 CMS, 5 maintainers and 6 restorers) were analyzed with 15 random amplification polymorphic DNA (RAPD) and 20 inter simple sequence repeat (ISSR) marker. Out of 15 RAPD markers, 9 were polymorphic and 79 bands were generated, of which 28 bands were polymorphic (35 %). By using 10 out of 20 ISSR markers 86 bands were detected, of which 35 bands were polymorphic (41 %). Marker index (RAPD = 1.68; ISSR = 1.88) and percent of polymorphic bands indicated that ISSR markers were relatively more efficient in polymorphism detection. Cluster analysis of the parents based on Jaccard’s genetic similarity and UPGMA method were revealed 3 groups. Restorer lines IR68061 and IR5931 with origin of the Philippines were found in distinct group. Results suggesting the cross between CMS lines Neda and Nemat with restorer lines IR68061 and IR5931, can be used as the best heterotic groups for exploration of heterosis.